(untitled) (Revista Cocar, 2021)
Esta pesquisa teve como objetivo compreender as representações sociais de indivíduos sobre a implantação dos colégios cívico-militares no Paraná. A pesquisa caracteriza-se como de abordagem qualitativa com delineamento documental. Foram analisados comentários feitos em uma publicação on-line de um WebJornal sobre a transformação de escolas públicas de educação básica em colégios cívico-militares. Os comentários selecionados foram analisados no software IRaMuTeQ, sendo submetidos à Classificação Hierárquica Descendente (CHD), que gerou três classes, e à análise de similitude, que separou o corpus textual em três clusters. Concluiu-se que as representações sociais dos sujeitos sobre a implantação dos colégios cívico-militares não são hegemônicas, embora os dados evidenciem que há um forte apelo popular pela militarização da educação. Palavras-chave: Representações sociais; Educação básica; Colégios cívico-militares. Abstract This research aimed at comprehending the individual social representations about the civic-military schools in Paraná. The research is characterized as a qualitative approach with documental outline. Were analyzed commentaries made on an on-line publication of a WebJournal about the transformation of public basic education schools into civic-military schools. The selected commentaries were analyzed in the IRaMuTeq Software, being submitted into the Descending Hierarchical Classification (DHC), that generated three classes, and into similitude analysis, that separated the textual corpus in three clusters. It was concluded that the individual social representations about the civic-military schools’ implantation are not hegemonic, although the data evidence that there is a strong popular appeal for the militarization of education. Keywords: Social representations; Basic education; Civic-military schools.